Association of streptomycin resistance mutations with level of drug resistance and Mycobacterium tuberculosis genotypes. - Nhu, N; Lan, N; Phuong, N; Chau, N; Farrar, J; Caws, M (2012)
OBJECTIVES: To determine 1) the relationship between specific streptomycin (SM) resistance mutations and the minimum inhibitory concentration (MIC), and 2) whether these mutations are preferentially associated with the Beijing genotype in Viet Nam. METHODS: A total of 131 consecutive Mycobacterium tuberculosis isolates resistant to either isoniazid (INH) or rifampicin (RMP), collected previously, were tested for SM resistance, spoligotyped and sequenced in the rpsL, rrs and gidB genes. The MIC for 50 mutants was also determined. RESULTS: Overall, 116/131 isolates were SM-resistant. The three most frequently occurring mutation sites in rpsL and rrs were at codon 43 of rpsL (72/116, 62.1%), rpsL88 (22/116, 18.9%) and rrs514 (8/116, 6.9%). Mutations in the rrs910 region were found in two isolates (1.7%), and three isolates had mutations in both rpsL and rrs (2.6%). gidB mutations were found in both resistant and susceptible strains. Among SM-resistant isolates resistant to INH/RMP, the Beijing genotype was strongly associated with rpsL43 mutation (aOR 23.6, 95%CI 2.9-193.4, P = 0.002). The median MIC for each mutation was as follows: rpsL43 = 256 μg/ml, rpsL88 = 16 μg/ml, 515 loop = 4 μg/ml, 910 region = 8 μg/ml, and double mutation = 256 μg/ml. We found a strong association between rpsL43 and high drug resistance levels, with all rpsL43 mutants having an MIC >256 μg/ml (P < 0.001).